The Truth Society : Science, Disinformation, and Politics in Berlusconi's Italy - Liston, Noelle Mole (Book collections on Project MUSE., 2020)
"This book seeks to understand how the late-twentieth-century era of Italian political spectacle, which regularly blurred fact and fiction, has shaped how people understand truth, particularly mass mediated information, and in turn, scientific knowledge and forms of governance"--